Cryptococcal meningoencephalitis. Issue 5975 (12th July 1975) - Martin, R A; Bates, D; Shaw, D A
Abstract : A patient was admitted to hospital with an apparent psychiatric disturbance. When she became stuporous the cerebrospinal fluid was cultured but proved sterile. The latex test showed that serum was positive for cryptococcal antigens, and cryptococcal meningoencephalitis was diagnosed. Amphotericin B was given but when she developed a toxic reaction it was replaced by flucytosine. She responded well to flucytosine alone and no side effects appeared on continued treatment. Cryptococcal meningitis may present as a psychiatric disturbance, and serological tests are invaluable aids to diagnosis.